Gestão empreendedora: uma proposta para a Biblioteca Pública Municipal de Marituba - NASCIMENTO, Cleissielle Pereira do (2019)
has a objective to evidence the importance of entrepreneurial management and the benefits achieved through it. With a look at the reality of public libraries, the study has shown through bibliographical analyzes how fundamental it becomes for society, and the possible difficulties faced by it daily. Through an exploratory approach carried out in the Municipal Public Library of Marituba named Professor Maria Luiza Rabelo Freire, conclusions obtained through theoretical analysis were strongly confirmed from the data obtained in field research. Through intense research on administration, entrepreneurship, intra-entrepreneurship and information science, we define entrepreneurial management in public libraries as the central line of research and how this type of management generates rise and development not only for the space itself, but also for the the location to which it is introduced. Therefore, the present study reveals how much the public libraries, and in particular the Municipal Public Library of Marituba needs to invest in varied factors, including in the management question, so that through this it becomes in its totality a unit of information in constant evolution, with an entrepreneurial character.